Characteristics, Properties and Analytical Methods of Amoxicillin: A Review with Green Approach - Marco, Bianca Aparecida de [UNESP]; Hisano Natori, Jessica Sayuri [UNESP]; Fanelli, Stefany [UNESP]; Totoli, Eliane Gandolpho [UNESP]; Nunes Salgado, Herida Regina [UNESP] (Taylor & Francis Inc, 2017)
Bacterial infections are the second leading cause of global mortality. Considering this fact, it is extremely important studying the antimicrobial agents. Amoxicillin is an antimicrobial agent that belongs to the class of penicillins; it has bactericidal activity and is widely used in the Brazilian health system. In literature, some analytical methods are found for the identification and quantification of this penicillin, which are essential for its quality control, which ensures maintaining the product characteristics, therapeutic efficacy and patient's safety. Thus, this study presents a brief literature review on amoxicillin and the analytical methods developed for the analysis of this drug in official and scientific papers. The major analytical methods found were high-performance liquid chromatography (HPLC), ultra-performance liquid chromatography (U-HPLC), capillary electrophoresis and iodometry and diffuse reflectance infrared Fourier transform. It is essential to note that most of the developed methods used toxic and hazardous solvents, which makes necessary industries and researchers choose to develop environmental-friendly techniques to provide enhanced benefits to environment and staff.
Keywords: Amoxicillin; analytical methods; antimicrobial; green chemistry; penicillins